FROM COMPLEX EVOLVING TO SIMPLE: CURRENT REVISIONAL AND ENDOSCOPIC PROCEDURES FOLLOWING BARIATRIC SURGERY - Ricardo ZORRON; Manoel Passos GALVÃO-NETO; Josemberg CAMPOS; Alcides José BRANCO; José SAMPAIO; Tido JUNGHANS; Claudia BOTHE; Christian BENZING; Felix KRENZIEN (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2016)
ABSTRACT Background: Roux-en-Y gastric bypass (RYGB) is a standard therapy in bariatric surgery. Sleeve gastrectomy and gastric banding, although with good results in the literature, are showing higher rates of treatment failure to reduce obesity-associated morbidity and body weight. Other problems after bariatric may occur, as band erosion, gastroesophageal reflux disease and might be refractory to medication. Therefore, a laparoscopic conversion to a RYGB can be an effective alternative, as long as specific indications for revision are fulfilled. Objective: The objective of this study was to analyse own and literature data on revisional bariatric procedures to evaluate best alternatives to current practice. Methods: Institutional experience and systematic review from the literature on revisional bariatric surgery. Results: Endoscopic procedures are recently applied to ameliorate failure and complications of bariatric procedures. Therapy failure following RYGB occurs in up to 20%. Transoral outlet reduction is currently an alternative method to reduce the gastrojejunal anastomosis. The diameter and volume of sleeve gastrectomy can enlarge as well, which can be reduced by endoscopic full-thickness sutures longitudinally. Dumping syndrome and severe hypoglycemic episodes (neuroglycopenia) can be present in patients following RYGB. The hypoglycemic episodes have to be evaluated and usually can be treated conventionally. To avoid partial pancreatectomy or conversion to normal anatomy, a new laparoscopic approach with remnant gastric resection and jejunal interposition can be applied in non-responders alternatively. Hypoglycemic episodes are ameliorated while weight loss is sustained. Conclusion: Revisional and endoscopic procedures following bariatric surgery in patients with collateral symptomatic or treatment failure can be applied. Conventional non-surgical approaches should have been applied intensively before a revisional surgery will be indicated. Former complex surgical revisional procedures are evolving to less complicated endoscopic solutions.